2016
DOI: 10.1155/2016/4618323
|View full text |Cite
|
Sign up to set email alerts
|

Novel Biomarker MicroRNAs for Subtyping of Acute Coronary Syndrome: A Bioinformatics Approach

Abstract: Acute coronary syndrome (ACS) is a life-threatening disease that affects more than half a million people in United States. We currently lack molecular biomarkers to distinguish the unstable angina (UA) and acute myocardial infarction (AMI), which are the two subtypes of ACS. MicroRNAs play significant roles in biological processes and serve as good candidates for biomarkers. In this work, we collected microRNA datasets from the Gene Expression Omnibus database and identified specific microRNAs in different sub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 86 publications
1
19
0
Order By: Relevance
“…Su et al (35) demonstrated that upregulating hsa-mir-142-3p could ameliorate myocardial ischemic injury. of note, hsa-mir-142-3p is considered to be a biomarker for acute Mi (36). in the present study, it was found that hsa-mir-142-3p was downregulated in the blood of patients with Mi.…”
Section: Discussionsupporting
confidence: 59%
“…Su et al (35) demonstrated that upregulating hsa-mir-142-3p could ameliorate myocardial ischemic injury. of note, hsa-mir-142-3p is considered to be a biomarker for acute Mi (36). in the present study, it was found that hsa-mir-142-3p was downregulated in the blood of patients with Mi.…”
Section: Discussionsupporting
confidence: 59%
“…Four groups of miRNAs are identified, which are involved in regulation of the CV system of which nearly 18 seem specific for AMI, for example miR-155, miR-34a, miR-126, miR-133a, miR-208b, and a few others show much promise as specific and accurate markers of dysfunction. 23…”
Section: Micrornas (Mirnas)mentioning
confidence: 99%
“…[16][17] It is also predicted that microRNA changes such as up-regulation or down-regulation occur at much earlier stages of disease development, while the accurate diagnosis of MI is a target for prognosis and treatment of patients. [18][19] In the current study, the predictive value of circulating microRNAs, including microRNA-1 and microRNA-221-3p, as informative markers for MI, was determined in 200 patients on their presentation to the emergency ward of a cardiovascular medical center using a 300-μl of whole blood sample. Both of the tested microRNAs significantly increased in patients with MI, even in cases whose symptoms were manifested within 1-12 hours or the ones with initially negative CTnI.…”
Section: Discussionmentioning
confidence: 99%
“…Due to its high sensitivity and specificity, it is proposed to use microRNA-221-3p as a biomarker to detect MI in patients with primary PCI in order to reduce mortality in the affected patients. 18,25 A c c e p t e d…”
Section: Discussionmentioning
confidence: 99%